Metastatic Non-Small-Cell Lung Cancer Presenting as Renal Failure From IgA Nephropathy - Samer Yassin MD; Sruthi Athota MD; Afnan Khan BS; Vraj Patel BS; James Williams MD; Suyash Dwivedi (SAGE Publishing, 2024)
Studies have highlighted a potential link between malignancies and immunoglobulin A nephropathy (IgAN). In such studies, the treatment of malignancy improved the symptoms of IgAN. Here, we report a patient case involving a history of hypertension, tobacco use disorder, and chronic kidney disease (CKD) presenting with hematuria with acute renal failure secondary to IgAN per renal biopsy. Prompted by this association, a malignancy workup was performed including computed tomography (CT) body imaging and biopsies of mediastinal and cervical lymph nodes which revealed a metastatic adenocarcinoma. Current knowledge includes a general mechanism behind the development of IgAN that points toward glomerular deposition of tumor-specific immunoglobulin A (IgA) immunoglobulins. However, the association of IgAN and malignancy has no definitive management guidelines. This clinical case serves as an important contribution in the hopes of future development of guidelines regarding the surveillance and management of IgAN in the setting of malignancy.